2013
DOI: 10.1155/2013/317487
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Literature Review: Recent Advances in Diagnosing and Managing Patients with Poorly Differentiated Thyroid Carcinoma

Abstract: Poorly differentiated thyroid carcinomas are a rare form of thyroid carcinomas; they display an intermediate behavior between well-differentiated and anaplastic thyroid carcinomas. PDTCs are more aggressive than the well-differentiated, but less aggressive than the undifferentiated or anaplastic, forms. No clinical features can accurately diagnose poorly differentiated thyroid carcinomas. Thus, the results of histocytology, immunohistochemistry, and molecular genetics tests aid in diagnosis. Given the aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 28 publications
1
40
0
5
Order By: Relevance
“…Survival rates are remarkably lower than in patients with WDTC [85,87,88]. Patients more than 45 years of age and those with cervical lymph node invasion, tumor necrosis, local recurrence, mitotic index greater than 3 per 10 high-power ields, tumor size greater than 4 cm, and distant metastasis at the time of diagnosis have poorer prognosis [89][90][91][92][13, 31-34].…”
Section: Poorly Diferentiated Thyroid Cancermentioning
confidence: 99%
“…Survival rates are remarkably lower than in patients with WDTC [85,87,88]. Patients more than 45 years of age and those with cervical lymph node invasion, tumor necrosis, local recurrence, mitotic index greater than 3 per 10 high-power ields, tumor size greater than 4 cm, and distant metastasis at the time of diagnosis have poorer prognosis [89][90][91][92][13, 31-34].…”
Section: Poorly Diferentiated Thyroid Cancermentioning
confidence: 99%
“…PDTCs are follicular-cell neoplasms that are morphologically and behaviorally intermediate between the well-differentiated FTC and PTC and the undifferentiated ATC. Interestingly, there are striking regional differences in PDTC incidence rates; Northern Italy has the highest rates (15 %) with much lower rates in the United States (1.8 %) and Japan (\1 %), suggesting a multifactorial causative interaction between genetics, environment, and diet [13]. A recent study has shown that insulin-like growth factor-I mRNA binding protein-3 (IMP3) expression in PDTC appears to be an adverse prognostic factor, in that in univariate analysis, the risk of death was higher for age C45, tumors C4 cm, and IMP3 positivity by immunohistochemistry [14].…”
Section: Dedifferentiationmentioning
confidence: 99%
“…e Poorly differentiated thyroid carcinoma arising in a well differentiated follicular variant papillary thyroid carcinoma (bottom left). f Anaplastic thyroid carcinoma ATCs are among the most lethal of all human malignancies and account for less than 3 % of thyroid cancers [13]. ATC is more common in females and in the elderly.…”
Section: Dedifferentiationmentioning
confidence: 99%
See 2 more Smart Citations